The validity of dysthymia to predict clinical depressive symptoms as measured by the Hamilton Depression Scale at the 5-year follow-up of patients with first episode depression. (16th November 2016) - Bech, Per; Kessing, Lars Vedel; Bukh, Jens Drachmann
Abstract: Background: In long-term follow-up studies on depression, the Eysenck Neuroticism Scale (ENS) at the score level of dysthymia has been found to be valid at predicting poor outcome. Aims: The ENS dysthymia level was compared with the Beck Depression Inventory (BDI) level to predict the prevalence of depressive symptoms at the 5-year follow-up of patients initially diagnosed with first episode depression using the Hamilton Depression Scale (HAM-D) to express depressive symptoms. Methods: A total of 301 in- or outpatients aged 18–70 years with a recent single depressive episode were assessed by ENS, BDI, and HAM-D from 2005–2007. At 5-year follow-up from 2011–2013, the participants were re-assessed by HAM-D. The HAM-D was used to measure depressive symptoms at the 5-year follow-up. The Mokken analysis was used to indicate scalability of the BDI and ENS. Results: A total of 185 participants were available for the psychometric analysis of the ESN and BDI, and the scalability was found acceptable. In total, 99 patients were available for the predictive analysis. Both the ENS and the BDI were significantly associated with depressive symptoms (HAM-D17  ≥  8) at the 5-year follow-up ( p  < 0.05). Conclusion: Dysthymia as measured by the two self-rating scales ENS and BDI can be considered part of a 'double depression' in patients with first episode depression, implying an existence of depressive symptoms at the 5-year follow-up. Clinical implications: Evaluation of dysthymia or neuroticism is important to perform, even in patients with first episode depression, in order to identify 'double depression'.